1999
DOI: 10.1007/s002510050550
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor Vbeta deletion and Valpha polymorphism are responsible for the resistance of SWR mouse to arthritis induction

Abstract: Collagen type II-induced arthritis (CIA) develops in susceptible mouse strains after intradermal injections of type II collagen (CII) in complete Freund's adjuvant (CFA). Susceptibility to CIA in mice is linked to genes of the major histocompatibility complex (MHC). Although the SWR mouse has a susceptible MHC haplotype (H2q), it is resistant to CIA. SWR exhibits at least two known immunological defects: (1) it contains a germline deletion of about 50% of T-cell receptor (TCR) Vbeta-chain gene segments, and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The T cell-mediated character of this disease was shown by transfer experiments. In support of this hypothesis, two polymorphisms in AV11 were recently suggested to be associated with susceptibility to arthritis in mice [29,30]. The important role of AV11 in collageninduced arthritis was further supported by protection studies using AV11 recombinant protein [28].…”
Section: Discussionmentioning
confidence: 88%
“…The T cell-mediated character of this disease was shown by transfer experiments. In support of this hypothesis, two polymorphisms in AV11 were recently suggested to be associated with susceptibility to arthritis in mice [29,30]. The important role of AV11 in collageninduced arthritis was further supported by protection studies using AV11 recombinant protein [28].…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that V␤8.2 is important in induction of CIA in H2A q mice. Absence of V␤8.2 TCR population in FVB mice is one of the reasons for nonsusceptibility to CIA (40). In vivo depletion of DW10 did not make the transgenic mice susceptible to arthritis suggesting that negative/positive selection of autoreactive cells occur in thymus and is probably influenced by polymorphism in MHC.…”
Section: Discussionmentioning
confidence: 99%
“…SJL/J, FVB/NJ, SWR, C57L, and C57BR strains have germline deletions in the Tcrb-V8 gene, with SJL/J mice having the largest amount of DNA deleted. 7,8,125 TCRB-V8 is expressed on many cell types, including natural killer T (NKT) cells and CD8þNKT cells. 40 NKT cells coexpress TCRB-V8 and the natural killer (NK) cell marker NK1.1 and thus represent a hybrid of the innate and adaptive immune system.…”
mentioning
confidence: 99%